The future of global currency : the euro versus the dollar - Cohen, Benjamin J. 4 0 16; 5 (London:;New York, NY : Routledge, 2011)
This collection distills the views of one of the world's leading scholars in global currency, and will be of considerable interest to students and scholars of international finance and international political economy. --Book Jacket.
Life at the top: international currencies in the twenty-first century -- The euro and transatlantic relations -- EMU and the dollar: who threatens whom? -- Global currency rivalry: can the euro ever challenge the dollar? -- Enlargement and the international role of the euro -- The euro in a global context: challenges and capacities -- Dollar dominance, euro aspirations: recipe for discord? -- A one-and-a-half currency system -- Toward a leaderless currency system -- The international monetary system: diffusion and ambiguity.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Euro.;Dollar.;International finance. -- 20; Foreign economic relations.;Foreign economic relations. -- European Union countries;United States -- 20; 2